The emerging role of m6A modification of non-coding RNA in gastrointestinal cancers: a comprehensive review - Wang, Meiqi; Liu, Zhuo; Fang, Xuedong; Cong, Xianling; Hu, Yue (Frontiers in Cell and Developmental Biology, 2023)
Gastrointestinal (GI) cancer is a series of malignant tumors with a high incidence globally.Although approaches for tumor diagnosis and therapy have advanced substantially, the mechanisms underlying the occurrence and progression of GI cancer are still unclear. Increasing evidence supports an important role for N 6 -methyladenosine (m 6 A) modification in many biological processes, including cancer-related processes via splicing, export, degradation, and translation of mRNAs. Under distinct cancer contexts, m 6 A regulators have different expression patterns and can regulate or be regulated by mRNAs and non-coding RNAs, especially long noncoding RNAs. The roles of m 6 A in cancer development have attracted increasing attention in epigenetics research. In this review, we synthesize progress in our understanding of m 6 A and its roles in GI cancer, especially esophageal, gastric, and colorectal cancers. Furthermore, we clarify the mechanism by which m 6 A contributes to GI cancer, providing a basis for the development of diagnostic, prognostic, and therapeutic targets.